Two Anti-inflammatory Steroidal Saponins from Dracaena angustifolia Roxb - Huang, Hui-Chi; Lin, Ming-Kuem; Hwang, Syh-Yuan; Hwang, Tsong-Long; Kuo, Yao-Haur; Chang, Chi-I; Ou, Chung-Yi; Kuo, Yueh-Hsiung (Molecules (Basel, Switzerland), 2013)
Two new steroidal saponins, named drangustosides A–B (1–2), together with eight known compounds 3–10 were isolated and characterized from the MeOH extract of Dracaena angustifolia Roxb. The structures of compounds were assigned based on 1D and 2D NMR spectroscopic analyses, including HMQC, HMBC, and NOESY. Compounds 1 and 2 showed anti-inflammatory activity by superoxide generation and elastase release by human neutrophils in response to fMLP/CB.